SOVEREIGN CREDIT RATING AND ITS IMPACT ON FOREIGN INVESTMENT AND GOVERNMENT DEBT: A CASE STUDY OF IRAQ AS A MODEL - Asaad Mohammed Ali Wahhab; Ali Khalaf Gatea; Mohammed Abd Ali M. A. AL Fattehallah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research discusses the relationship between the credit rating of Iraq and its impact on foreign direct investment flows for the period 2010-2018. In addition, the extent of the credit rating affects the flow of investments and its relationship to other factors that affect economic stability. The researchers relied on data issued by official institutions (the World Bank. International Monetary Fund. Central Bank reports. Iraq Stock Exchange). After analyzing the data and information,it was found that the correlation and effect, e.g. affected. There are three main factors that control foreign investment, foremost of which is the credit rating of recipient countries. As investments are usually directed to countries with a high credit rating, whether in the form of companies or mutual investment between the two countries (bilateral agreements). Or by free flow from low-rated countries to highly-rated recipient countries. Or, a credit rating with a regional dimension and geographical location qualifies the country to receive foreign Investment despite the average credit rating. The researchers recommend the need for the Sovereigns. to pay attention to improving the credit rating of Iraq. as it reflects a good image among Investors. the possibility of entering the Iraqi market and direct investment in it. And exploiting the investment opportunities available in the Iraqi companies listed. On the stock market.